PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI IPS 2 SMA NEGERI 1 GEGER TAHUN AJARAN 2012/2013 - Alfian Wicaksono; Supri Wahyudi Utomo; Satrijo Budi Wibowo (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study was to knowing the motivation and learning outcomes of students of class XI IPS 2 SMA N 1 Geger after learning implemented using type STAD cooperative learning to improve motivation and learning outcomes of accounting students. This research is empirical research. The collection data in this study were obtained through the questionnaire method, the method of testing, and documentation. Analysis of the data used to analyze the research data is a simple analysis technique.  In action research, the researcher conducted two cycles in a single class. Each cycle performed by the procedure of planning, action, observation and reflection. The data was collected using a questionnaire sheet motivation and test questions. Sheet motivation questionnaire to determine students' motivation for learning activities, while about a test conducted at the end of each cycle of learn that is used to determine student learning outcomes. Based on the comparison of cycle I and II, it can be concluded that learning to type STAD cooperative learning model can improve motivation, students' class XI IPS 2 SMA N 1 Geger.